Exploring informal education for promoting mental health literacy: a study to youth in Malaysia - Badruldin, Muhammad Nur Waafi; Hamzah, Siti Raba’ah; Aziz, Faiq; Muhamad Nasharudin, Nurfazreen Aina (Human Resource Management Academic Research Society, 2021)
The study aimed to explore the role of informal education in promoting mental health literacy among Malaysian youth. Semi-structured interviews were conducted with six practitioners and group focus interviews with university youth. The comprehensive view of the role of informal education in promoting mental health literacy that emerged from the interviews included family members providing emotional support and social therapy. In addition, nongovernmental organizations promote mental health management methods and other activities related to mental health literacy, role from peers with socialising others, and mass media become an influencer to the youth, social media page related to mental health has a positive influence on youth, expert and caregiver officers act actively by performing the process of recognizing, acknowledge and contribute. The themes found addressed the understanding of promoting mental health literacy among youth in Malaysia.